Adsorption of Lead (Pb) Ions from Workshop Wastewater Using a Combined Filter of Coconut Shell Charcoal, Pumice, and Hair Waste - Marlinang Isabella Silalahi; Ermi Girsang; Agung Abadi Kiswandono; Hartono; Putranto Manalu (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
The abundance of natural materials has attracted the attention of numerous researchers, who are now developing them into effective adsorbents for waste treatment applications. The waste stream in question includes laundry liquid waste from workshops, which is discharged directly into the environment via soil or drainage channels without any form of pretreatment. The lead content (Pb) in workshop laundry liquid waste is hazardous if discharged into the environment because it is difficult to degrade. This study investigates a filtration media composed of a combination of natural adsorbents—coconut shell charcoal, pumice stone, and hair waste as an option for treating workshop laundry liquid waste. This research was conducted in January 2021 and focuses specifically on its effectiveness in reducing Pb levels. Adsorbents are arranged in a 60 cm diameter barrel with a height of 40 cm for each adsorbent. Laboratory analysis for the lead test method according to SNI 6989.8.2009 with Atomic Absorption Spectrophotometry (SSA) shows a decrease in Pb levels starting from the control to the first repetition, second repetition, and third repetition, where the final results show that Pb levels are safe to be discharged into the environment because they are below the environmental quality standards based on the Regulation of the Minister of Environment of the Republic of Indonesia Number 5 of 2014 concerning Wastewater Quality Standards, which is a maximum of 0.03 mg/L. Filtration A showed a Pb level of 0.021 (50% decrease), and Filtration B showed a Pb level of 0.106 (80% decrease)